Belgian Politics and the Spanish Civil War - Vargas Visús, Jorge (Hispania Nova, 2021)
During the second half of the 1930s, Belgium and its institutions were about to undergo testing. The first serious test came about after the shocking results of the legislative elections held on May 24, 1936. Léon Degrelle’s party, the Rex, gained 21 seats. Consequently, a new coalition government had to be constituted in order to safeguard political stability. In parallel with this, a redefinition of the European political landscape was taking place due to the effects caused by the remilitarization of the Rhineland in March 1936. Vis-à-vis that new European scenario, the Belgian government decided upon a new foreign policy that aimed at liberating the country of its international commitments enshrined in the Versailles and Locarno treaties.Both political levels were narrowly connected, influencing each other. Given this connection the Belgian political debate was distorted when it was transferred to the realm of emotions provoked by the Spanish conflict.
Keywords: Belgium; Locarno Treaty; Paul-Henri Spaak; Politique d’indépendance; Spanish Civil War